Dose Distribution near Tissue In-homogeneities in Megavoltage Radiation Therapy - Katsarou, E.; Karava, K.; Stamatelatos, I. E.; Kalef-Ezra, J. (HNPS Advances in Nuclear Physics, 2019)
The presence of an in-homogeneity inside the human body modifies the radiation dose distribution in tissue. Such disturbances are even higher close to the interface between materials of different atomic number, Z. During radiotherapy with megavolt photons a remarkable lack of particle equilibrium is displayed in the transition zones between soft tissues and either bones or devices implanted in the human body for medical purposes, resulting in large dose gradients. The disturbance in the dose distribution in soft tissue close to a high Z material in regions where the photon beam enters or exits the in-homogeneity, is quantified by the Backscatter Dose Factor (BSDF) and Forward Scatter Dose Factor (FSDF), respectively. In the present work BSDF and FSDF dependence on photon energy, material thickness, atomic number and field size were studied experimentally. For this purpose, slabs made of high Z material (aluminum, copper and lead) were inserted in a PMMA (Plexiglas) phantom. Irradiations were performed using a Co-60 teletherapy unit and two 6 MV linear accelerators. Dose measurements were carried out using MD-55 and HD-810 Gafchromic films. The results of the study showed that the presence of the in-homogeneity increased the absorbed dose in the low Z material before the in-homogeneity (BSDF >1.00) and decreased after it (FSDF <1.00). Moreover, it was found that BSDF increases as the in-homogeneity thickness increases (up to a saturation thickness). On the contrary, FSDF decreases with increasing in-homogeneity thickness. In addition, both disturbances increase with increasing Z of the in-homogeneity. Outcome of this study was high quality experimental data to be used for benchmarking BSDF and FSDF calculations performed by dedicated Monte Carlo and analytical radiotherapy treatment planning systems.